Answer:
2(x+1)= 2x+2.
Step-by-step explanation:
Because, there is a on infront of x so you do 2x1=2 so 2x+2 because 2x1=2
Answer:
y=-2x^2-4
Step-by-step explanation:
The parabola is wider than it's parent function, y = x^2. Therefore the coefficient, of x^2 (when you refer to quadratic equations it's a) should be greater than 1. Let's take 2.
y = 2x^2
Now it is reflected across the x-axis, so the equation turns to y = -2x^2. The vertex is shifted down 4. Note that it is shifted down, along the y-axis. This makes 'c' (again quadratic equations) -4.
Final Equation: y=-2x^2-4
The answer is 296 hope it helps
16.445 I have no expectation sorry.